Biochar regulates enzymes activity and interspecies electron transfer to promote bioenergy recovery from a continuous two-stage food waste anaerobic digestion process. (20th January 2023) - Yuan, Tugui; Sun, Ran; Shao, Mingshuai; Chen, Qindong; Lin, Yeqi; Xu, Qiyong
Abstract: The influence of biochar on the performance of food waste anaerobic digestion in a continuous two-stage process was examined. Biochar was added to a methanogenic (MG) reactor, with 50% of its effluent recirculated to a hydrolytic–acidogenic (HA) reactor. The addition of biochar in the MG reactor simultaneously enhanced the performance of both reactors, and the energy recovery efficiency increased by 25.01–70.99%. Biochar improved the activities of protease and α-amylase in the HA and MG reactors by 1.08–2.23 and 0.46–1.21, and 13.65–15.76 and 8.73–13.64 times, respectively. The enhancement of these hydrolytic enzymes' activity in the HA reactor was correlated to the effluent recirculation from the MG reactor, contributing to the improved hydrolysis of food waste. Furthermore, the activity of coenzyme F420 in the MG reactor increased by 11.47%, 18.81%, and 27.03%, respectively, indicating that biochar can promote hydrogenotrophic methanogenesis. Microbial analysis revealed that the presence of biochar promoted interspecies hydrogen transfer between Syntrophomonas and hydrogenotrophic methanogens. Additionally, biochar triggered direct interspecies electron transfer between Geobacter sulfurreducens and acetotrophic methanogens, enabling effective methanogenesis. Graphical abstract: Image 1